PENGARUH GAYA HIDUP TERHADAP MINAT BELI SMARTPHONE VIVO PADA MASYARAKAT DESA JAHARUN B DUSUN 1 KECAMATAN GALANG KABUPATEN DELI SERDANG - Riska Ananda Azhhari; Yayuk Yuliana (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
The purpose of this study was to find out how to analyze the influence of Lifestyle (X) on Interest in Buying (Y) Vivo smartphones in the people of Jaharun B Village, Dusun 1, Galang District, Deli Serdang Regency with a total sample of 97 people. The data collection technique used is by using a questionnaire or questionnaire given to each respondent. The data is processed using SPSS 20. The data analysis technique used is simple linear regression (b) of 0.737 and it can be concluded that Lifestyle has a significant positive effect on Purchase Interest. Which means that if the Lifestyle is increasing, the Buying Interest will increase by 0.737. Based on the t test, it is known that tcount ttable is 11,037 1,661. So it can be stated that there is a real influence between Lifestyle and Interest in Buying Vivo smartphones in the Jaharun B Village Community, Dusun 1, Galang District, Deli Serdang Regency, and the relationship is proven to be significant. From the results of the coefficient of determination (R square) it can be said that the Lifestyle variable (X) has an effect on the Purchase Interest variable (Y) of 0.562 or with a percentage of 56.2% and the remaining 43.8% is influenced by other variables not examined by research this.